Software and Hardware Decision Support System for Operators of Electrical Power Systems; IEEE Transactions on Power Systems; Vol. 36, iss. 5 - Ruban N. Yu. Nikolay Yurievich; Suvorov A. A. Aleksey Aleksandrovich; Andreev M. V. Mikhail Vladimirovich; Ufa R. A. Ruslan Alexandrovich; Askarov A. B. Alisher Bakhramzhonovich; Gusev A. S. Alexander Sergeevich; Bhalja B. R. Bhavesh (2021, 2021)
Title screen